2015
DOI: 10.1212/wnl.0000000000002176
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular vs medical management of acute ischemic stroke

Abstract: Objective: To compare the outcomes between endovascular and medical management of acute ischemic stroke in recent randomized controlled trials (RCT).Methods: A systematic literature review was performed, and multicenter, prospective RCTs published from January 1, 2013, to May 1, 2015, directly comparing endovascular therapy to medical management for patients with acute ischemic stroke were included. Meta-analyses of modified Rankin Scale (mRS) and mortality at 90 days and symptomatic intracranial hemorrhage (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 31 publications
3
102
0
5
Order By: Relevance
“…It was noted that the distribution of Cog-4 scores was better in patients who received intravenous recombinant tissue plasminogen activator compared to those who were not thrombolysed, although this scale did not provide additional information beyond the modified Rankin Scale (mRS) assessment. 6 Endovascular treatment has recently demonstrated benefit in physical disability and functional outcome after acute stroke, 7 but the effect on cognitive outcomes has not been established yet. REVASCAT (Endovascular Revascularization With Solitaire Device Versus Best Medical Therapy in Anterior Circulation Stroke Within 8 Hours) randomized acute stroke patients either to medical therapy plus endovascular treatment thrombectomy or to medical treatment alone.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…It was noted that the distribution of Cog-4 scores was better in patients who received intravenous recombinant tissue plasminogen activator compared to those who were not thrombolysed, although this scale did not provide additional information beyond the modified Rankin Scale (mRS) assessment. 6 Endovascular treatment has recently demonstrated benefit in physical disability and functional outcome after acute stroke, 7 but the effect on cognitive outcomes has not been established yet. REVASCAT (Endovascular Revascularization With Solitaire Device Versus Best Medical Therapy in Anterior Circulation Stroke Within 8 Hours) randomized acute stroke patients either to medical therapy plus endovascular treatment thrombectomy or to medical treatment alone.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…As this procedure requires trainees to manipulate the microcatheter and microwire and eventually deploy stents in intracranial vessels in addition to the placement of a guiding catheter, perfusion, and imaging, they can learn basic techniques of endovascular treatment. In addition, mechanical thrombectomy has been reported to be effective as a treatment for acute-phase cerebral infarction, [13][14][15][16] and shortening of the time until recanalization is a condition for improving the outcome. Therefore, simulation training in thrombectomy is considered to contribute to improvements in the clinical effectiveness and safety of catheter treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, five studies reported strong evidence that intraarterial interventions (intraarterial thrombolysis, mechanical clot retrieval, or both) combined with standard medical management improves the outcomes of appropriately selected patients with AIS and large artery occlusion [17]. A subsequent metaanalysis that included pre-2015 studies confirmed that endovascular thrombectomy is associated with higher rates of angiographic revascularization and improved functional outcomes, but it found no significant difference in symptomatic intracranial hemorrhage or all-cause mortality at 90 days after large artery occlusion-related AIS [18].…”
Section: Strokementioning
confidence: 99%